Election Supervisory Board as the Constitutional Watchdog: Ensuring Human Rights and Electoral Neutrality in Indonesia - Wahyu Donri Tinambunan; Maharani Nurdin; Adi Kristian Silalahi; Souad Ahmed Ezzerouali (Faculty of Law Universitas Jenderal Soedirman, 2025)
The integrity of Indonesia’s democratic elections depends on the impartial enforcement of electoral laws and the protection of citizens’ political rights. The Election Supervisory Board (Bawaslu), although not explicitly established in the Constitution, serves as a key institution mandated by statutory law to oversee electoral neutrality and protect the fairness of electoral processes. Its supervisory mandate intersects with broader constitutional principles and human rights norms, particularly in addressing violations of political neutrality by state officials and safeguarding the right to political participation. This study aims to critically analyze the extent to which Bawaslu incorporates constitutional oversight and human rights considerations into its supervisory practices and how these frameworks influence its effectiveness. Using a normative legal research method with statutory, conceptual, and comparative approaches, the study evaluates national legal instruments, Bawaslu regulations, and selected case studies. Findings indicate that Bawaslu’s oversight capacity is constrained by gaps in legal clarity, inconsistent inter-institutional coordination, and the absence of explicit constitutional grounding for its human rights obligations. Strengthening its institutional independence, refining the legal framework, and aligning domestic electoral oversight with international human rights standards are crucial steps for enhancing both electoral integrity and political neutrality. Beyond the Indonesian context, this study contributes to the global discourse on the role of non-constitutional electoral oversight bodies in consolidating democratic governance, offering comparative insights relevant to emerging democracies worldwide.